Modulation of autoimmune arthritis severity in mice by apolipoprotein E (ApoE) and cholesterol. (4th October 2016) - Alvarez, P; Genre, F; Iglesias, M; Augustin, J J; Tamayo, E; Escolà-Gil, J C; Lavín, B; Blanco-Vaca, F; Merino, R; Merino, J
Summary: Apolipoprotein E (ApoE) deficiency promoted an exacerbation of autoimmune arthritis in mice by inducing proinflammatory immune responses. In this study we analysed the contribution of hypercholesterolaemia and/or the absence of ApoE anti-inflammatory properties, unrelated to its function in the control of cholesterol metabolism, towards the acceleration of arthritis in these mutant animals. The induction and severity of collagen type II-induced arthritis (CIA) were compared for B10.RIII wild-type (WT), B10.RIII. ApoE +/–, B10.RIII. ApoE –/– and B10.RIII.low-density lipoprotein receptor ( LDLR –/– ) mice with different concentrations of circulating ApoE and cholesterol. A 50–70% reduction in serum levels of ApoE was observed in heterozygous B10.RIII. ApoE +/– mice in comparison to B10.RIII.WT, although both strains of mice exhibited similar circulating lipid profiles. This ApoE reduction was associated with an increased CIA severity that remained lower than in homozygous B10.RIII. ApoE –/– mice. An important rise in circulating ApoE concentration was observed in hypercholesterolaemic B10.RIII. LDLR –/– mice fed with a normal chow diet, and both parameters increased further with an atherogenic hypercholesterolaemic diet. However, the severity of CIA in B10.RIII. LDLR –/– mice was similar to that of B10.RIII.WT controls. In conclusion, by comparing the evolution of CIA between several strains of mutant mice with different levels of serum ApoE and cholesterol, our results demonstrate that both hypercholesterolaemia and ApoE regulate the intensity of in-vivo systemic autoimmune responses. Graphical Abstract: